SANKSI ADAT BAJA BIMA SEBAGAI ALTERNATIF HUKUMAN PELAKU KORUPSI DI KABUPATEN BIMA NUSA TENGGARA BARAT - Mohammad Irfan; H. Israfil (Unram Law Review, 2017)
Purpose of this study are to find out Baja custom value as an effort to minimalize factors that cause high number of corruption in Bima district of West Nusa Tenggara province. Furthermore to explain the implementation Baja sanction as an alternative punishment for the corruptor in Bima district of West Nusa Tenggara province. This research use socio legal method which is combine qualitative and quantitative. Result of the research are; that Baja custom sanction is very important to be implemented since the corruption crime to the district budget of revenue and expenditure is so massive, by revitalize norms of Baja custom and summarized it in an awig-awig (customary law) that applied in all villages in district of Bima of West Nusa Tenggara province. Implementation of the sanction of Baja custom as an alternative punishment for the corruptor is keeping by activate and maximize the role of the custom institution such as Majelis sara Tua. Revitalization should be planned by the district government and supported by the society.